2011
DOI: 10.1002/jps.22681
|View full text |Cite
|
Sign up to set email alerts
|

Local epicardial inotropic drug delivery allows targeted pharmacologic intervention with preservation of myocardial loading conditions

Abstract: Local myocardial application of inotropes may allow the study of pharmacologically augmented central myocardial contraction in the absence of confounding peripheral vasodilating effects and alterations in heart loading conditions. Novel alginate epicardial (EC) drug releasing platforms were used to deliver dobutamine to the left ventricle of rats. Pressure volume analyses indicated that while both local and systemic (IV) use of inotropic drugs increase stroke volume and contractility, systemic infusion does so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…PV conductance catheters can be used as a continuous real-time monitor of cardiovascular function but such use is more complicated and somewhat more limited than at specific points in time. Continuous experiments are often pharmacologic interventions that produce acute haemodynamic changes, on the order of minutes to hours, and can be performed while the PV catheter remains in situ for the duration of the treatment [10, 11]. We have found that such real-time monitoring during pharmacologic treatment can only be performed with frequent manipulation to optimise position, which can lead to disruptions in continuous signals.…”
Section: Introductionmentioning
confidence: 99%
“…PV conductance catheters can be used as a continuous real-time monitor of cardiovascular function but such use is more complicated and somewhat more limited than at specific points in time. Continuous experiments are often pharmacologic interventions that produce acute haemodynamic changes, on the order of minutes to hours, and can be performed while the PV catheter remains in situ for the duration of the treatment [10, 11]. We have found that such real-time monitoring during pharmacologic treatment can only be performed with frequent manipulation to optimise position, which can lead to disruptions in continuous signals.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated favorable pharmacokinetics, with elevated myocardial drug levels and minimal peripheral concentration, when drug is given to the pericardial sac [23–28]. We have shown in small animals that local EC application of inotropic compounds leads to elevated myocardial drug and intracellular second messenger concentrations in target ventricular tissue, enhanced contractile response with lower systemic levels, and less atrial and peripheral vascular responses than IV infusion [29, 30]. EC epinephrine delivery in rats required only 1/3 rd of the IV dose rate to provide an equal contractile effect without raising plasma drug levels or deleterious systemic side effects such as tachycardia or peripheral vasodilation [30].…”
Section: Introductionmentioning
confidence: 83%
“…1a). This diffusion may be in equilibrium with clearance from capillaries and enzymatic degradation [13, 18] so that as long as the release continues, the gradient will persist. Local delivery may flood the tissue with drug; some small fraction binds to specific receptors and activates biological effect while the majority remains unbound.…”
Section: Discussionmentioning
confidence: 99%
“…A novel polymeric local epicardial (EC) drug releasing system designed to permit precise animal-weight based epinephrine release to the anterior wall of the beating rat heart was fabricated from calcium-cross-linked alginate hydrogels [18]. Briefly, 45 mcl of 2% alginate (#71238, Sigma-Aldrich) slurry in double distilled water (ddH20) was pipetted onto the upper side of the permeable membrane of a transwell support (#3472, 6.5mm, polyester, 3 micrometers pore size; Corning).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation